Preparation method of mesoporous carbon material

By utilizing the carbon source in new minerals and combining alkali leaching, acid leaching and adhesive high-temperature activation methods, mesoporous carbon materials with high specific surface area and narrow pore size distribution are prepared, which solves the problem of complex preparation and high cost in the existing technology. problem, achieving simple, low-cost and environmentally friendly preparation of mesoporous carbon materials.

CN119330343APending Publication Date: 2025-01-21BEIJING YIXING TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411433924.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art has problems of complex synthesis, high cost and use of toxic substances when preparing mesoporous carbon materials, which limits its industrial applications.

Method used

The new type of mineral is used as raw materials, and components such as alkaline immersion and acid immersion removal of silicon dioxide formation to form a touches, carbon maintains the original state, combined with adhesion and high temperature activation, prepare high -ratio surface area and narrow -pores distributed media carbon material Essence

Benefits of technology

The simple, low-cost and environmentally friendly preparation of mesoporous carbon materials is achieved. The produced mesoporous carbon has appropriate pore size and uniformity, and is suitable as a carrier for adsorbents and catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330343A_ABST
    Figure CN119330343A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a mesoporous carbon material. The preparation method comprises the following steps: stirring, dispersing and scattering mineral raw materials to form slurry; the mineral raw materials comprise crystalline components and amorphous components, the crystalline components account for 78% of the mineral mass fraction, and the amorphous components account for 21% of the mineral mass fraction; the crystalline component comprises quartz, pyrite, kaolinite and mica, and the quartz accounts for 91% of the mass fraction of the crystalline component; the amorphous substance comprises water, elemental carbon and an organic matter, and the elemental carbon accounts for 95% of the mass fraction of the amorphous component; carrying out repeated nanocrystallization grinding on the slurry to prepare nanoscale mineral slurry; treating the nanoscale mineral slurry to prepare carbon powder; treating the carbon powder to obtain high-purity carbon powder; mixing the high-purity carbon powder with a certain amount of adhesive, and then carrying out gluing treatment to prepare glued carbon powder; and calcining the glued carbon powder to prepare the mesoporous carbon material. The preparation method is simple in technological process, the mesoporous carbon is prepared in a gluing and high-temperature activation mode, and the preparation method is low in production cost and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of mineral processing technology, and more specifically, to a technical method for preparing mesoporous carbon materials using new minerals as raw materials. The present invention belongs to the field of fine processing of non-metallic minerals, and in particular, to a method for preparing mesoporous carbon materials. Background Art

[0002] Mesoporous carbon materials refer to porous carbon materials with pore sizes ranging from 2 to 50 nm. They have extremely high specific surface area, regular and orderly pore structure, narrow pore size distribution, and continuously adjustable pore size. Mesoporous carbon materials are materials with a variety of application prospects and are widely used in adsorption, catalysis, energy storage, drug controlled release and other fields.

[0003] The template method is currently the most commonly used method for preparing mesoporous carbon materials. In the process of synthesizing mesoporous carbon materials using the template method, the structure of the mesoporous carbon material can be controlled by changing the spatial size, shape and structural order of the template. However, there are also problems such as complex synthesis, high cost, and the need to use toxic substances in the preparation process, which greatly limits the industrial application of mesoporous carbon materials. Therefore, it is of great significance to find a simple, low-cost, and environmentally friendly method for preparing mesoporous carbon.

[0004] In nature, carbon is widely present in various minerals. However, in the actual production process, these carbons are generally treated as impurities and removed by calcination and other methods, and are not fully utilized. Exploring the methods and mechanisms of constructing mesoporous carbon materials using natural minerals as carbon sources will provide a simple, low-cost, and pollution-free method for preparing mesoporous carbon materials, and realize the high-value utilization of carbon in minerals. Summary of the invention

[0005] In order to solve the technical defects and deficiencies in the prior art, the present invention provides the following technical solutions: a method for preparing a mesoporous carbon material, based on the composition of a new type of mineral, a method for preparing mesoporous carbon using a new type of mineral as a raw material is provided, the new type of mineral selected in the method contains carbon and silicon dioxide, the two grow together, and the silicon dioxide and other components are removed by alkali leaching and acid leaching, and the removed components form pores in situ, and the carbon maintains its original state, and the overall mesoporous carbon structure is formed, and then through gluing and activation, a mesoporous carbon material with a high specific surface area and a narrow pore size distribution can be prepared. The obtained mesoporous carbon has a suitable pore size and a uniform pore, and the carbon material can be used as a carrier for an adsorbent and a catalyst due to its characteristic adsorption effect on organic matter.

[0006] The present invention provides a method for preparing a mesoporous carbon material, comprising the following steps:

[0007] S1, stirring, dispersing and breaking up the mineral raw materials to form a slurry; wherein the mineral raw materials include crystalline components and amorphous components, the crystalline components account for 78% of the mineral mass fraction, and the amorphous components account for 21% of the mineral mass fraction; the crystalline components include quartz, pyrite, kaolinite and mica, and quartz accounts for 91% of the crystalline components by mass; the amorphous substances include water, elemental carbon and organic matter,

[0008] Elemental carbon accounts for 95% of the mass fraction of the amorphous component;

[0009] S2, repeatedly nano-grinding the slurry to prepare a nano-scale mineral slurry;

[0010] S3, treating the nano-scale mineral slurry to prepare carbon powder;

[0011] S4, processing the carbon powder to obtain high-purity carbon powder;

[0012] S5, mixing the high-purity carbon powder with a certain amount of adhesive and performing a bonding process to prepare bonded carbon powder;

[0013] S6, calcining the bonded carbon powder to prepare a mesoporous carbon material.

[0014] Preferably, the S1 comprises:

[0015] S11, with d 75 Minerals with a diameter of less than 10 μm are used as raw materials, and the raw materials are processed into mineral powders;

[0016] S12, placing the mineral powder in a high-speed disperser for strong stirring and dispersion to form dispersed mineral powder;

[0017] S13, adding a certain amount of water and an appropriate amount of grinding aid to the dispersed mineral powder to form a first mixed liquid;

[0018] S14, placing the first mixed solution in a high-speed stirring disperser and dispersing it for a first time;

[0019] Preferably, the mass ratio of the dispersed mineral powder: water: grinding aid = 100: (100-500): (0.5-5); the grinding aid is sodium polyacrylate, triethanolamine or sodium hexametaphosphate; and the first time is 0.5h-4h.

[0020] Preferably, S2 includes:

[0021] S21, pumping the slurry into a bead mill for nano-grinding;

[0022] S22, repeatedly grinding the slurry in a bead mill until the slurry has 90<100nm, nano-scale mineral slurry can be produced.

[0023] Preferably, the grinding media used in the nano-grinding are zirconium oxide ceramic beads or aluminum oxide ceramic beads; the size of the grinding media is φ0.03-0.4 mm; and the filling rate of the grinding media in the grinding cavity is 65%-80%.

[0024] Preferably, S3 includes:

[0025] S31, extracting and purifying the nano-scale mineral slurry to obtain an extract;

[0026] S32, filtering, drying and breaking up the upper layer of the extract in sequence to prepare carbon powder.

[0027] Preferably, the extraction and purification process uses kerosene, hexadecyltrimethylammonium bromide or oleic acid as an extractant; the mass ratio of the nano-scale mineral slurry: the extractant = 1: (0.02-0.5).

[0028] Preferably, S4 includes:

[0029] S41, adding the carbon powder into a certain amount of water to form a second mixed liquid;

[0030] S42, adding an alkaline leaching agent and an acid leaching agent to the second mixed solution in sequence to perform chemical leaching and purification treatment to obtain a purified slurry;

[0031] S43, filtering, drying and breaking up the purified slurry to obtain high-purity carbon powder.

[0032] Preferably, the alkaline leaching agent is sodium hydroxide or potassium hydroxide; the acid leaching agent is hydrochloric acid, sulfuric acid or nitric acid; the mass ratio of the carbon powder: water: alkaline leaching agent = 20: (100-500): (1-20); the carbon powder: water: acid leaching agent = 20: (20-500): (50-300); the reaction temperature of the chemical leaching and purification treatment is 50°C-95°C, and the reaction time of the chemical leaching and purification treatment is 1h-12h.

[0033] Preferably, the adhesive is epoxy resin E51 or epoxy resin E44; the mass ratio of the high-purity carbon powder:adhesive=10:(0.1-15).

[0034] Preferably, S6 includes:

[0035] S61, placing the bonded carbon powder in a tube furnace;

[0036] S62, forming a nitrogen atmosphere in the tubular furnace, and calcining the bonded carbon powder at a high temperature in the nitrogen atmosphere to obtain a mesoporous carbon material.

[0037] Preferably, the temperature of the high-temperature calcination is 400° C. to 800° C., and the constant temperature time of the high-temperature calcination is 0.5 h to 3 h.

[0038] Beneficial effects of the present invention:

[0039] (1) Innovatively utilize carbon in minerals as a carbon source and use physical methods to prepare it into mesoporous carbon, which has the advantages of simple method, environmentally friendly process and low cost.

[0040] (2) The preparation method has a simple process flow, and mesoporous carbon is prepared by gluing and high-temperature activation. The production cost is low and environmentally friendly. Mesoporous carbon materials can be prepared to obtain pore sizes between 2nm and 50nm and a specific surface area of ​​80m 2 / g or more mesoporous carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a flow chart of the preparation method of the mesoporous carbon material provided by the present invention.

[0042] Figure 2 The flowchart of step S1 provided by the present invention.

[0043] Figure 3 The flowchart of step S2 provided by the present invention.

[0044] Figure 4 The flowchart of step S3 provided by the present invention.

[0045] Figure 5 The flowchart of step S4 provided by the present invention.

[0046] Figure 6 This is a flow chart of step S6 provided by the present invention.

[0047] Figure 7 This is a scanning electron microscope image of the mesoporous carbon provided by the present invention. DETAILED DESCRIPTION

[0048] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0049] like Figure 1-6 As shown, this embodiment provides a method for preparing a mesoporous carbon material, comprising the following steps:

[0050] S1, stirring, dispersing and breaking up the mineral raw materials to form a slurry;

[0051] The mineral raw material used in this embodiment is a natural mineral, which is black in appearance, and the main mineral components are silicon dioxide and carbon, and trace organic matter, wherein the silicon dioxide and carbon are combined with each other to form a mesoporous structure, and have great utilization value. The method of the present invention includes the steps of removing the crystalline components in the novel mineral with acid and alkali, and gluing and activating the mineral at high temperature, and mesoporous carbon can be obtained by removing silicon dioxide and organic matter therein, and then gluing and activating at high temperature.

[0052] As a preferred embodiment, the mineral raw material includes a crystalline component and an amorphous component, the crystalline component accounts for 78% of the mineral mass fraction, and the amorphous component accounts for 21% of the mineral mass fraction; the crystalline component includes quartz, pyrite, kaolinite and mica, and quartz accounts for 91% of the mass fraction of the crystalline component; the amorphous substance includes water, elemental carbon and organic matter, and elemental carbon accounts for 95% of the mass fraction of the amorphous component.

[0053] As a preferred embodiment, the S1 includes:

[0054] S11, with d 75 Minerals with a diameter of less than 10 μm are used as raw materials, and the raw materials are processed into mineral powders;

[0055] S12, placing the mineral powder in a high-speed disperser for strong stirring and dispersion to form dispersed mineral powder;

[0056] S13, adding a certain amount of water and an appropriate amount of grinding aid to the dispersed mineral powder to form a first mixed liquid;

[0057] S14, placing the first mixed solution in a high-speed stirring disperser and dispersing it for a first time;

[0058] As a preferred embodiment, the mass ratio of the dispersed mineral powder: water: grinding aid is 100:

[0059] (100~500):(0.5~5); the grinding aid is sodium polyacrylate, triethanolamine or sodium hexametaphosphate; the first time is 0.5h~4h.

[0060] Reducing the mass ratio of mineral powder is conducive to the dispersion of mineral powder in the slurry and improving the efficiency of breaking up, but adding too much water will increase the production cost. If the breaking up time is too short, the particle size of the mineral powder may be large, affecting grinding, and if it is too long, the particle size is difficult to further reduce. The grinding mechanism of the three grinding aids is to reduce the agglomeration effect of particles. Sodium polyacrylate is a long-chain molecule, one end of which is adsorbed with the activation point on the surface of the mineral powder particles, and the long-chain molecule at the other end can increase the steric hindrance between the particles, thereby playing a dispersing role; triethanolamine is also an organic molecule, which can have a weak steric hindrance effect to prevent particle agglomeration; sodium hexametaphosphate belongs to the inorganic salt grinding aid, which changes the chemical environment of the system during the grinding process, introduces a large number of acid radicals and ions into the water, and can change the double layer and zeta potential of the particle surface to a certain extent, reducing agglomeration. The addition of different grinding aids can effectively reduce the particle size of the product. In the embodiment of the present invention, the grinding effect of sodium polyacrylate is better than that of sodium hexametaphosphate, and sodium hexametaphosphate is better than that of triethanolamine.

[0061] Therefore, as a more preferred embodiment, the grinding aid is sodium polyacrylate; the mass ratio of the dispersed mineral powder: water: grinding aid is 100: (100-300): (1-2), and the first time is 1h-2h.

[0062] S2, repeatedly nano-grinding the slurry to prepare a nano-scale mineral slurry;

[0063] As a preferred embodiment, S2 includes:

[0064] S21, pumping the slurry into a bead mill for nano-grinding;

[0065] As a preferred embodiment, the grinding media used in the nano-grinding are zirconium oxide ceramic beads or aluminum oxide ceramic beads; the size of the grinding media is φ0.03-0.4 mm; and the filling rate of the grinding media in the grinding cavity is 65%-80%.

[0066] Alumina and zirconia ceramic beads are the most commonly used grinding media at present, among which zirconia beads have higher hardness and strength than alumina beads; alumina beads are less expensive and their performance can meet the requirements of this experiment. The size of the grinding medium affects the grinding limit of the particles. The smaller the relative particle size of the particles, the lower the probability of being collided during the grinding process, and the more energy is lost by the mutual friction between the grinding media themselves during the grinding process. Therefore, when performing nano-grinding, the size of the grinding medium needs to be reduced accordingly. However, the medium size is also limited by the grinding equipment and cannot be too small. If the grinding medium filling rate is too high, it may affect the service life of the equipment. If it is too low, the frequency of collision between the grinding medium and the particles will be reduced, affecting the grinding efficiency. Therefore, as a more preferred embodiment, the grinding medium used for the nano-grinding is zirconia ceramic beads, and the size of the grinding medium is Φ

[0067] 0.03mm~0.2mm, and the filling rate of the grinding medium in the grinding cavity is 70%~80%.

[0068] S22, repeatedly grinding the slurry in a bead mill until the slurry has 90 <100nm, nano-scale mineral slurry can be produced.

[0069] S3, treating the nano-scale mineral slurry to prepare carbon powder;

[0070] As a preferred implementation, S3 includes:

[0071] S31, extracting and purifying the nano-scale mineral slurry to obtain an extract;

[0072] As a preferred embodiment, the extraction and purification process uses kerosene, hexadecyltrimethylammonium bromide or oleic acid as an extractant; the mass ratio of the nano-scale mineral slurry: extractant = 1: (0.02-0.5).

[0073] Oleic acid is an anionic extractant, hexadecyltrimethylammonium bromide is a cationic one, and kerosene is a non-polar one. Different types of extractants can be used for different types of carbon-containing minerals. When the amount of extractant is small, only part of the carbon can be adsorbed by the extractant, and the rest of the carbon will be lost as tailings, so it is necessary to increase the amount of extractant added. However, in the present invention, there is a limit to the extraction rate, and continuing to increase the amount of extractant cannot further improve the extraction rate, which may cause a waste of the extractant. Therefore, as a more preferred embodiment, the extraction and purification process uses kerosene as the extractant; the mass ratio of the nanoscale mineral slurry: extractant = 1:

[0074] (0.05~0.2).

[0075] S32, filtering, drying and breaking up the upper layer of the extract in sequence to prepare carbon powder.

[0076] S4, processing the carbon powder to obtain high-purity carbon powder;

[0077] As a preferred implementation, S4 includes:

[0078] S41, adding the carbon powder into a certain amount of water to form a second mixed liquid;

[0079] S42, adding an alkaline leaching agent and an acid leaching agent to the second mixed solution in sequence to perform chemical leaching and purification treatment to obtain a purified slurry;

[0080] As a preferred embodiment, the alkaline leaching agent is sodium hydroxide or potassium hydroxide; the acid leaching agent is hydrochloric acid, sulfuric acid or nitric acid; the mass ratio of the carbon powder: water: alkaline leaching agent = 20: (100-500): (1-20); the carbon powder: water: acid leaching agent = 20: (20-500): (50-300); the reaction temperature of the chemical leaching and purification treatment is 50°C-95°C, and the reaction time of the chemical leaching and purification treatment is 1h-12h.

[0081] The alkaline leaching and acid leaching reagents are both acid and alkali reagents commonly used in chemical leaching. In the present invention, sodium hydroxide and hydrochloric acid introduce fewer impurity ions to the mineral powder. Increasing the concentration of the leaching agent, the reaction temperature, and the reaction time can all improve the purity of the product, but the purity of the product obtained by this method has a limit, and when the purity is high enough, further improving the purity has a limited effect on the improvement of the performance of mesoporous carbon, and the selection of the above parameters also needs to take into account the production cost. Therefore, as a more preferred embodiment, the alkaline leaching agent is sodium hydroxide, the acid leaching agent is hydrochloric acid, the mass ratio of the carbon powder: water: alkaline leaching agent = 20: (100-300): (5-10), the carbon powder: water: acid leaching agent = 20: (100-300): (50-200), the reaction temperature of the chemical leaching purification treatment is 75°C-95°C, and the reaction time of the chemical leaching purification treatment is 3h-6h.

[0082] S43, filtering, drying and breaking up the purified slurry to obtain high-purity carbon powder.

[0083] S5, mixing the high-purity carbon powder with a certain amount of adhesive and performing bonding treatment to prepare bonded carbon powder.

[0084] As a preferred embodiment, the adhesive is epoxy resin E51 or epoxy resin E44; the mass ratio of the high-purity carbon powder to the adhesive is 10:(0.1-15).

[0085] Compared with epoxy resin E44, epoxy resin E51 has lower viscosity, higher fluidity, and is better mixed with mineral powder. When the amount of epoxy resin added is low, appropriately increasing the amount added is more conducive to the formation of a mesoporous structure in the mineral powder, but adding too much epoxy resin will make it difficult to remove it, and even block the pores, reducing the performance of the mesoporous carbon product. Therefore, as a more preferred embodiment, the adhesive is epoxy resin E51, and the mass ratio of the high-purity carbon powder: adhesive = 10: (0.5~2).

[0086] S6, calcining the bonded carbon powder to prepare a mesoporous carbon material.

[0087] As a preferred implementation, S6 includes:

[0088] S61, placing the bonded carbon powder in a tube furnace;

[0089] S62, forming a nitrogen atmosphere in the tubular furnace, and calcining the bonded carbon powder at a high temperature in the nitrogen atmosphere to obtain a mesoporous carbon material.

[0090] As a preferred embodiment, the temperature of the high-temperature calcination is 400° C. to 800° C., and the constant temperature time of the high-temperature calcination is 0.5 h to 3 h.

[0091] Increasing the calcination temperature can enhance the activation of carbon powder and promote the development of pores, but when the temperature is too high, the pore structure will be destroyed, and micropores and mesopores will develop into macropores. When the constant temperature time is short, the micropores in the carbon material are still developing and the structure has not yet opened; when the optimal activation time is exceeded, the pore size continues to increase, the micropores develop into macropores, and even penetrate the mesoporous carbon structure, resulting in a decrease in specific surface area. Here, "constant temperature time" refers to the time that the heating equipment is kept warm at the selected calcination temperature, i.e., calcined. Therefore, as a more preferred embodiment, the temperature of the high-temperature calcination is 400°C to 600°C, and the constant temperature time of the high-temperature calcination is 0.5h to 2h.

[0092] like Figure 7 The figure shows a scanning electron microscope image of the mesoporous carbon prepared in the embodiment of the present invention. The mesoporous carbon is prepared by gluing and high-temperature activation, which has low production cost and is environmentally friendly. The prepared mesoporous carbon material has a pore size distribution between 2nm and 50nm and a specific surface area of ​​80m 2 / g or more mesoporous carbon,

[0093] Application Examples

[0094] Example 1

[0095] This embodiment provides a method for preparing mesoporous carbon, comprising the following steps:

[0096] 1) The new mineral powder (d 90 =11.44μm, d 75 =8.69μm) was added into a certain amount of water, and sodium polyacrylate was added as a grinding aid, the mass ratio of mineral powder: water: grinding aid = 100:100:0.5, and the mixture was dispersed in a high-speed stirring disperser for 4h.

[0097] 2) Add Φ0.03 mm alumina grinding media into the nano bead mill with a filling rate of 80%, and then pump the slurry prepared in 1) into the bead mill storage tank. Grind the material repeatedly in the bead mill until d 90 After the particle size is less than 100 nm, the slurry is pumped out to obtain nano-scale mineral slurry.

[0098] 3) Using kerosene to extract and purify the ore pulp obtained in 2), the mass ratio of ore pulp: extractant = 1: 0.02. Filter, dry and break up the upper layer of liquid obtained by extraction to obtain carbon powder.

[0099] 4) Add the carbon powder obtained in step 3) to a certain amount of water, and use sodium hydroxide and hydrochloric acid to perform chemical leaching and purification treatment, the mass ratio of mineral powder: water: alkaline leaching agent = 20: 100: 1, mineral powder: water: acid leaching agent = 20: 20: 50. The reaction temperature is 50°C and the reaction time is 1h. The purified slurry is filtered, dried and dispersed to obtain high-purity carbon powder.

[0100] 5) The high-purity carbon powder obtained in step 4) is mixed with a certain amount of adhesive epoxy resin E51 for bonding, with the mass ratio of mineral powder: adhesive = 10:0.1.

[0101] 6) The bonded carbon powder obtained in step 5) is placed in a tube furnace and calcined at high temperature under a nitrogen atmosphere to obtain a mesoporous carbon material. The calcination temperature is 400°C, the constant temperature time is 0.5h, and the specific surface area of ​​the obtained mesoporous carbon is 37m 2 / g, average pore size 9nm.

[0102] Example 2

[0103] This embodiment provides a method for preparing mesoporous carbon, comprising the following steps:

[0104] 1) The new mineral powder (d 90 =5.22μm) was added into a certain amount of water, and sodium polyacrylate was added as a grinding aid, the mass ratio of mineral powder: water: grinding aid = 100:500:5, and the mixture was dispersed in a high-speed stirring disperser for 0.5h.

[0105] 2) Add Φ0.4 mm alumina grinding media to the nano bead mill with a filling rate of 65%, and then pump the slurry prepared in 1) into the bead mill storage tank. Grind the material repeatedly in the bead mill until d 90 After the particle size is less than 100 nm, the slurry is pumped out to obtain nano-scale mineral slurry.

[0106] 3) Using kerosene to extract and purify the ore pulp obtained in 2), the mass ratio of ore pulp: extractant = 1:0.5. Filter, dry and break up the upper layer of liquid obtained by extraction to obtain carbon powder.

[0107] 4) Add the carbon powder obtained in step 3) to a certain amount of water, and use sodium hydroxide and hydrochloric acid to perform chemical leaching and purification treatment, the mass ratio of mineral powder: water: alkaline leaching agent = 20: 300: 20, mineral powder: water: acid leaching agent = 20: 500: 300. The reaction temperature is 95°C and the reaction time is 12h. The purified slurry is filtered, dried and dispersed to obtain high-purity carbon powder.

[0108] 5) The high-purity carbon powder obtained in step 4) is mixed with a certain amount of adhesive epoxy resin E51 for bonding, with the mass ratio of mineral powder: adhesive = 10:15.

[0109] 6) The bonded carbon powder obtained in step 5) is placed in a tube furnace and calcined at high temperature under a nitrogen atmosphere to obtain a mesoporous carbon material. The calcination temperature is 800°C, the constant temperature time is 3h, and the specific surface area of ​​the obtained mesoporous carbon is 57m 2 / g, average pore size 18nm.

[0110] Example 3

[0111] This embodiment provides a method for preparing mesoporous carbon, comprising the following steps:

[0112] 1) The new mineral powder (d 90 =9.13μm) was added into a certain amount of water, and sodium polyacrylate was added as a grinding aid, the mass ratio of mineral powder: water: grinding aid = 100:200:1.5, and the mixture was dispersed in a high-speed stirring disperser for 1h.

[0113] 2) Add Φ0.1 mm zirconium oxide grinding media to the nano bead mill with a filling rate of 70%, and then pump the slurry prepared in 2) into the bead mill storage tank. Grind the material repeatedly in the bead mill until d 90 After the particle size is less than 100 nm, the slurry is pumped out to obtain nano-scale mineral slurry.

[0114] 3) Using kerosene to extract and purify the ore pulp obtained in 2), the mass ratio of ore pulp: extractant = 1:0.1. Filter, dry and break up the upper layer liquid obtained by extraction to obtain carbon powder.

[0115] 4) Add the carbon powder obtained in step 3) to a certain amount of water, and use sodium hydroxide and hydrochloric acid to perform chemical leaching and purification treatment, the mass ratio of mineral powder: water: alkaline leaching agent = 20: 200: 5, mineral powder: water: acid leaching agent = 20: 200: 150. The reaction temperature is 90°C and the reaction time is 5 hours. The purified slurry is filtered, dried and dispersed to obtain high-purity carbon powder.

[0116] 5) The high-purity carbon powder obtained in step 4) is mixed with a certain amount of adhesive epoxy resin E51 for bonding, with the mass ratio of mineral powder: adhesive = 10:1.

[0117] 6) The bonded carbon powder obtained in step 5) is placed in a tube furnace and calcined at high temperature under a nitrogen atmosphere to obtain a mesoporous carbon material. The calcination temperature is 500°C, the constant temperature time is 1 hour, and the specific surface area of ​​the obtained mesoporous carbon is 83m 2 / g, average pore size 12nm.

[0118] Although preferred embodiments of the present invention have been described, additional changes and modifications may be made to these embodiments by those skilled in the art once the basic inventive concepts are known. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a mesoporous carbon material, characterized in that: The steps include: S1, stirring, dispersing and breaking up the mineral raw materials to form a slurry; wherein the mineral raw materials include crystalline components and amorphous components, the crystalline components account for 78% of the mineral mass fraction, and the amorphous components account for 21% of the mineral mass fraction; the crystalline components include quartz, pyrite, kaolinite and mica, and quartz accounts for 91% of the crystalline components by mass; the amorphous substances include water, elemental carbon and organic matter, and the elemental carbon accounts for 95% of the amorphous components by mass; S2, repeatedly nano-grinding the slurry to prepare a nano-scale mineral slurry; S3, treating the nano-scale mineral slurry to prepare carbon powder; S4, processing the carbon powder to obtain high-purity carbon powder; S5, mixing the high-purity carbon powder with a certain amount of adhesive and performing a bonding process to prepare bonded carbon powder; S6, calcining the bonded carbon powder to prepare a mesoporous carbon material.

2. The method for preparing a mesoporous carbon material according to claim 1, characterized in that: The S1 includes: S11, with d 75 Minerals with a diameter of less than 10 μm are used as raw materials, and the raw materials are processed into mineral powders; S12, placing the mineral powder in a high-speed disperser for strong stirring and dispersion to form dispersed mineral powder; S13, adding a certain amount of water and an appropriate amount of grinding aid to the dispersed mineral powder to form a first mixed liquid; S14, placing the first mixed solution in a high-speed stirring disperser and dispersing it for a first time.

3. The method for preparing a mesoporous carbon material according to claim 2, characterized in that: The mass ratio of the dispersed mineral powder: water: grinding aid=100: (100-500): (0.5-5); the grinding aid is sodium polyacrylate, triethanolamine or sodium hexametaphosphate; the first time is 0.5h-4h.

4. The method for preparing a mesoporous carbon material according to claim 3, characterized in that: The S2 includes: S21, pumping the slurry into a bead mill for nano-grinding; S22, repeatedly grinding the slurry in a bead mill until the slurry has 90 <100nm, nano-scale mineral slurry can be produced.

5. The method for preparing a mesoporous carbon material according to claim 4, characterized in that: The grinding media used in the nano-grinding are zirconium oxide ceramic beads or aluminum oxide ceramic beads; the size of the grinding media is φ0.03-0.4 mm; and the filling rate of the grinding media in the grinding cavity is 65%-80%.

6. The method for preparing a mesoporous carbon material according to claim 5, characterized in that: The S3 includes: S31, extracting and purifying the nano-scale mineral slurry to obtain an extract; S32, filtering, drying and breaking up the upper layer of the extract in sequence to prepare carbon powder.

7. The method for preparing a mesoporous carbon material according to claim 6, characterized in that: The extraction and purification process uses kerosene, hexadecyltrimethylammonium bromide or oleic acid as an extractant; the mass ratio of the nano-scale mineral slurry: the extractant is 1: (0.02-0.5).

8. The method for preparing a mesoporous carbon material according to claim 7, characterized in that: The S4 includes: S41, adding the carbon powder into a certain amount of water to form a second mixed liquid; S42, adding an alkaline leaching agent and an acid leaching agent to the second mixed solution in sequence to perform chemical leaching and purification treatment to obtain a purified slurry; S43, filtering, drying and breaking up the purified slurry to obtain high-purity carbon powder.

9. The method for preparing a mesoporous carbon material according to claim 8, characterized in that: The alkaline leaching agent is sodium hydroxide or potassium hydroxide; the acid leaching agent is hydrochloric acid, sulfuric acid or nitric acid; the mass ratio of the carbon powder: water: alkaline leaching agent is 20: (100-500): (1-20); the carbon powder: water: acid leaching agent is 20: (20-500): (50-300); the reaction temperature of the chemical leaching and purification treatment is 50°C-95°C, and the reaction time of the chemical leaching and purification treatment is 1h-12h.

10. The method for preparing a mesoporous carbon material according to claim 9, characterized in that: The adhesive is epoxy resin E51 or epoxy resin E44; the mass ratio of the high-purity carbon powder to the adhesive is 10:(0.1-15).

11. The method for preparing a mesoporous carbon material according to claim 10, characterized in that: The S6 includes: S61, placing the bonded carbon powder in a tube furnace; S62, forming a nitrogen atmosphere in the tubular furnace, and calcining the bonded carbon powder at a high temperature in the nitrogen atmosphere to obtain a mesoporous carbon material.

12. The method for preparing a mesoporous carbon material according to claim 11, characterized in that: The temperature of the high-temperature calcination is 400° C. to 800° C., and the constant temperature time of the high-temperature calcination is 0.5 h to 3 h.